2022
DOI: 10.18820/2519593x/pie.v40.i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Academic and institutional readiness towards e-Learning to inform policy and practice in an evolving post-school education sector

Abstract: Prior to the occurrence of the global COVID-19 pandemic, some African higher education institutions had already adopted a hybridmode for all their programmes, including distance education. Policies and strategies were put in place to improve the practices, skills and competencies of staff and students. However, the closure of education institutions globally due to the pandemic resulted in the rethinking of current education practices and highlighted the inherent inequalities in the system. This baseline qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another study by Akbarilakeh et al ( 2019) showed that university workers were happy with the e-learning method [44].…”
Section: Attitude Towards Distance Learning During Covid-19mentioning
confidence: 99%
“…Another study by Akbarilakeh et al ( 2019) showed that university workers were happy with the e-learning method [44].…”
Section: Attitude Towards Distance Learning During Covid-19mentioning
confidence: 99%
“…However, the implementation of these technologies in higher education in Africa to satisfy the need for e-Learning should take serious steps of assessment to measure their readiness level. E-Learning readiness is required to ensure the users can use the e-Learning environment and associated technology in the best way possible (Omidire & Aluko, 2022). Adopting novel learning technologies like e-Learning at any university usually comes with readiness and motivation to accept and learn new things related to its application (Almas et al, 2021).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Anderson and Rivera-Vargas (2020) argue that there has been an increased prevalence of online learning in the DNA of ODL. Investments in the development of staff, information and communication technology (ICT), infrastructure, and resources have constantly been made to best leverage the affordances of the online learning environment (Omidire & Aluko, 2022). The benefits of online learning are well documented in the literature in bridging the distance between the institution and the student by providing immediate access to study materials and the lecturer, interactive learning environments, and the opportunity for students to manage their own learning journey (Kara et al, 2019;Olson & Carroll, 2012;Venkatesh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, ODL institutions are constantly deliberating on how best to harness and leverage the benefits of current information and communication technologies. Omidire and Aluko (2022) argue that reviewing strategies, practices, and online learning design in ODL is necessary. Pre-and post-pandemic research on online learning within the ODL space has increased its relevance, making it prudent to build on existing knowledge about theory, practical experiences, and knowledge (Bozkurt & Zawacki-Richter, 2021).…”
Section: Introductionmentioning
confidence: 99%